What Makes an Excellent Teacher? Insights From Junior High School Students With a History of Disruptive Behavior - Graham, Linda J.; Tancredi, Haley; Gillett-Swan, Jenna (Frontiers in Education, 2022)
Evidence of the powerful relationship between what teachers do and how effectively their students learn has led to reforms aimed at improving the quality of teaching. Most jurisdictions are now paying increased attention both to the initial and ongoing education of teachers, as well as methods to assess, reward and improve quality teaching. Predominant among these methods are frameworks that define observable elements of pedagogical practice for which there is evidence of benefit for student learning, engagement, and behavior. However, we contend that even the best of these do not go far enough, as they do not explicitly consider students with disability, even those students with so-called “high-incidence” disabilities enrolled in everyday classrooms—such as those with Attention Deficit Hyperactivity Disorder and Developmental Language Disorder—whose classroom behavior often indicates that their learning needs are not being met. In this manuscript, we report findings from in-depth interviews with 50 Grade 7–10 students with a history of disruptive and disengaged behavior from three secondary schools serving disadvantaged communities. Responses to the question “what makes an excellent teacher” were coded into four categories. Three of the four categories (emotional support, classroom organization, and instructional support) reflect internationally accepted domains of quality teaching, while the fourth, teachers’ temperament and personality, was added to gauge accuracy of the common belief that this is the element students care most about. Analysis yielded novel results with the majority of students emphasizing instructional support practices that are not well represented in most measures of quality teaching. We argue that these practices represent an essential—but often absent—“top layer” of clarity and accessibility that is necessary for “quality teaching” to be inclusive teaching.